Self-assessment of the mental health of medical secondary school students - Nikolic, Nevena; Stojanovic, Goran; Jezdimirovic, Danijela; Čantrak, Tamara; Terzić Marković, Dragana (Education and Research in Health Sciences, 2025)
Introduction: Mental health is the basis of every person's health and is mostly related to the personal development of the individual. Adolescence is a crucial period that will determine the success of an individual's physical and mental development, which can be impaired by poor mental health. Some of the most common mental health disorders in adolescence are depression, risky sexual behaviour, addictions, etc. Prevention of mental disorders and promotion of mental health are important concepts aimed at reducing the incidence of mental problems, conducted through strategies at different social levels.Objective: To examine the attitudes and self-assessment of mental health of high school studentsMethods: The attitudes and self-assessment of mental health of the students were determined by a survey containing 24 questions and a standardized PHQ 9 questionnaire consisting of nine segments where the students had the opportunity to circle one of the four answers offered. The survey included a sample of 80 students from the "Medical School of Cacak".Results: The results of the study showed that all the subjects considered it equally important to care for mental health as well as physical health. Peer pressure, which was cited by 33.8% of students, is the most common obstacle in seeking mental health assistance. According to the standardised scale of the results of the PHQ9 questionnaire, over 32% of the subjects showed mild depressive symptoms.Conclusion: The results of the study led to the conclusion that large majorities of students consider mental health support services to be insufficiently available, and that peer pressure is a major obstacle in seeking support. Besides that, a third of the students surveyed showed signs of minimal level of depression.
Keywords: mental health; students; self-assessment; adolescence; PHQ-9 questionnaire